2018
DOI: 10.14520/adyusbd.381005
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Çokkültürlülüğe İlişkin Algılarının Farklı Değişkenler Açısından İncelenmesi

Abstract: Multiculturalism includes becoming aware of races, ethnic structures, languages, sexual orientations, gender, age, being disabled, social classes, education, religious orientations and other cultural dimensions. Teachers who play a significant role in the educational process should also be trained to have the necessary competence in multiculturalism. The aim of the study was to investigate first-and third-year teacher candidates' perceptions of multiculturalism in terms of different variables. Since it was aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Bu nedenle öğretmenlerin tüm akademik kurumlarda iletişim becerileri, bireysel ya da gruba yönelik çalışmaları ve çokkültürlülükle ilgili farklı bakış açılarını ele alan çeşitli türde yöntem, teknik ve yaklaşımları kullanmaları önemlidir (Alazzi, 2016). Ayrıca Türkiye'de artan sığınmacı/göçmen sayısındaki artışa paralel olarak çokkültürlülükle ilgili yapılan çalışmaların arttığı ve özellikle öğretmenlerin bu kavrama yönelik yeterliklerinin incelendiği görülmektedir (Akkaya, Susar-Kırmızı ve İşçi, 2018;Başbay, Kağnıcı ve Başbay, 2018;Bulut ve Başbay;Durşen-Ünal, 2018;Tonbuloglu, Aslan ve Aydın, 2016).…”
Section: Resultsunclassified
“…Bu nedenle öğretmenlerin tüm akademik kurumlarda iletişim becerileri, bireysel ya da gruba yönelik çalışmaları ve çokkültürlülükle ilgili farklı bakış açılarını ele alan çeşitli türde yöntem, teknik ve yaklaşımları kullanmaları önemlidir (Alazzi, 2016). Ayrıca Türkiye'de artan sığınmacı/göçmen sayısındaki artışa paralel olarak çokkültürlülükle ilgili yapılan çalışmaların arttığı ve özellikle öğretmenlerin bu kavrama yönelik yeterliklerinin incelendiği görülmektedir (Akkaya, Susar-Kırmızı ve İşçi, 2018;Başbay, Kağnıcı ve Başbay, 2018;Bulut ve Başbay;Durşen-Ünal, 2018;Tonbuloglu, Aslan ve Aydın, 2016).…”
Section: Resultsunclassified
“…On the contrary, it has been observed that the research in the international field is at a stage in which the practices and the experience related to this process are examined in line with the prevalence of multicultural education practices (Baltes, Hernandez & Collins, 2015;Golub, 2014;Guth, McAuliffe & Michalak, 2014;Perveen, 2014). Studies conducted on multiculturality in Turkey generally show that teacher candidates, teachers, administrators and academics are positive in multiculturality and multicultural education (Akkaya, Kırmızı & İşçi, 2018;Alanay & Aydın, 2016;Avcı & Faiz, 2018;Başarır, Sarı & Çetin, 2014;Damgacı & Aydın, 2013;Kahraman & Sezer, 2017;Polat, 2012), although there are many deficiencies in curricula and textbooks (Akar & Keyvanoğlu, 2016;Akhan & Yalçın, 2016;Çayır, 2016;Keskin & Yaman, 2014;Seban & Uyanık, 2016). Therefore, education policies in Turkey are still not equipped to bring multiculturality into educational environments (Köşker & Özgen, 2018).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…It has been observed that the most studied subjects are the perceptions (e.g. Akar, 2017;Akkaya, Susar Kırmızı & İşçi, 2018;Başarır, Sarı & Çetin, 2014;Marangoz, Aydın & Adıgüzel, 2015), attitudes (e.g. Durmuş, 2017;Güleç, 2019;Güngör, Buyruk & Özdemir, 2018;Kaba, 2019;Kervan, 2017;Koçak & Özdemir, 2015;Köşker & Özgen, 2018;Onur Sezer & Bağçeli Kahraman, 2017;Siviş, 2019) and competencies (e.g.…”
Section: Multicultural Education In Social Studies Coursementioning
confidence: 99%